PENGARUH KONVERGENSI IFRS DAN KEPEMILIKAN ASING TERHADAP TIMELY LOSS RECOGNITION - Liliek Nur Sulistiyowati; Robby Sandhi Dessyarti; Adi Gunanto (INVENTORY: JURNAL AKUNTANSI, 2018)
This research is intended to analyzeinfluence of convergence of International Financial Reporting Standard (IFRS) and foreign ownership to Timely Loss Recognition (TLR) at trade and service company listed in Bursa Efek Indonesia (BEI). This research comparing between before and after the IFRS convergence of the level loss recognition and see whether there is an increase in therecognition of a loss on time with the presence of foreign ownership within the company.Researchers used four control variables, namely firm size, profitability, leverage, and audit quality. TLR is measured by the ratio of Large Negative Net Income.This research used purposive sampling method at companies listed on BEI from 2014 until 2016, there are13 samples and tested by using linear regression.The results of this research indicate thatthere was an influence between IFRS convergence and foreign ownership of TLR. Control variable, leverage variable and audit quality indicatesignificant influence. This research has once again indicatethat the application of IFRS has an impact on improving the quality of accounting information and the demand for timely recognition of losses in less than stackholder financial statements.